Molecular Detection of Virulence Genes among Escherichia coli Isolated from Poultry Faecal Samples - Telugu, Venkata Padmavathi; Putturu, Ramya; Chinta, Siva Swetha; Devalam, Rani Prameela; Yasarla, Suresh; Eevuri, Tirupathi Reddy (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Shiga toxin-producing Escherichia coli (STEC) is known as a crucial zoonotic food-borne pathogen. The main virulence factor of STEC is the production of Shiga toxins 1 and 2. A total of 400 poultry faecal samples were collected from different poultry farms in and around Tirupathi, Andhra Pradesh. The samples were cultured in selective and differential culture media, and the virulence genes of E. coli isolates were analyzed by PCR assay. Out of 400 poultry faecal samples, 170 isolates were isolated and confirmed as E. coli by different biochemical tests with an overall prevalence of 42.5%. Out of 170 E. coli isolates 154 (90.5%) were found positive by targeting uspA gene with an amplification of 884 bp. All the 154 PCR confirmed E. coli isolates subjected to multiplex PCR for the detection of virulent genes targeting eae A, stx 1 and stx 2 and obtained an amplification products, respectively at 384 bp, 180 bp and 254 bp. Out of 154 E. coli isolates, 54 (35.06%) isolates had eae A gene, 36 (23.37 %) had stx 1 gene, 41 (26.62 %) isolates had stx 2 gene, 16 (3.89 %) isolates had both eae A & stx 2, and 12 (7.79%) isolates had both stx 1 & stx 2. By avoiding contact with contaminated faeces and by maintaining proper hygienic measures at farm, contamination of poultry and poultry products may be avoided which in turn may safeguard the health of public.